Peran Guru Dalam Upaya Meningkatkan Kedisiplinan Anak Di TK Nurfadilah Kota Kendari - Aris Suziman; Nur Lian (FKIP UNSULTRA, 2025)
Teacher efforts, efforts made by teachers as professional educators in educating, guiding, directing, and evaluating students by developing all the potential that exists in students, both in terms of cognitive (intelligence), affective (attitude), and psychomotor (skills) . PAUD teacher Nur Fadilah educates his students with discipline, so researchers want to see the efforts made by teachers in instilling discipline in children. The results of the study show that (1) The discipline of children in Kindergarten Nurfadilah when lining up before entering class, getting used to tidying up toys after use, washing hands before and after eating, has been applied by educators using a habituation approach. (2) the teacher's efforts in instilling discipline in children at Nur Fadilah Kindergarten, which is in accordance with the approach used, which includes exemplary methods, storytelling methods, (3) factors that influence teacher efforts in instilling discipline in children in Nur Fadilah Kindergarten are internal factors includes: the child's physical condition, psychological state, external factors include: family circumstances, and the environment.